2008
DOI: 10.3390/molecules13123198
|View full text |Cite
|
Sign up to set email alerts
|

Gastric and Duodenal Antiulcer Activity of Alkaloids: A Review

Abstract: Peptic ulcer disease is a deep gastrointestinal erosion disorder that involves the entire mucosal thickness and can even penetrate the muscular mucosa. Numerous natural products have been evaluated as therapeutics for the treatment of a variety of diseases, including this one. These products usually derive from plant and animal sources that contain active constituents such as alkaloids, flavonoids, terpenoids, tannins and others. The alkaloids are natural nitrogen-containing secondary metabolites mostly derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(57 citation statements)
references
References 47 publications
0
56
0
1
Order By: Relevance
“…They are known for their antimalarial, antimicrobial, cytotoxic and antiulcer properties. [25] Cytotoxic compounds are potentially interesting on their own or as lead compounds for the development of new anti-cancer drugs as well as drugs against parasites and viral infections. Through the use of GCMS, the S. portulacastrum containing these compounds may serve as a potential source of bioactive compounds in the prevention or cure of microbial and other disorders.…”
Section: Discussionmentioning
confidence: 99%
“…They are known for their antimalarial, antimicrobial, cytotoxic and antiulcer properties. [25] Cytotoxic compounds are potentially interesting on their own or as lead compounds for the development of new anti-cancer drugs as well as drugs against parasites and viral infections. Through the use of GCMS, the S. portulacastrum containing these compounds may serve as a potential source of bioactive compounds in the prevention or cure of microbial and other disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids and alkaloids protect the gastric mucosa against a variety of ulcerogenic agents in different mammalian species (de Sousa Falcão et al, 2008;Mota et al, 2009). Several mechanisms have been proposed to explain the gastroprotective effect of flavonoids; these include anti-secretory, cytoprotective and antioxidant activity (Mota et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…It is important to mention that several alkaloids present anti-ulcer activity [21]. Toma et al [22], showed that the alkaloids present in Senecio brasiliensis are able to increase mucus secretion and prostaglandin production in gastric mucosa.…”
Section: Resultsmentioning
confidence: 99%